PENGARUH KUALITAS TIDUR TERHADAP TEKANAN DARAH PADA LANSIA BERDASARKAN SKOR PITTSBURGH SLEEP QUALITY INDEX (PSQI) DI PUSKESMAS SUKAMAKMUR KABUPATEN ACEH BESAR - Fia Dewi Auliani; Rila Mariefni (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Sleep is an important factor for quality of life. Every individual has different sleep needs both in quality and quantity. Poor sleep quality can affect the balance of the hormone cortisol, which causes an increase in blood pressure. Blood pressure is the force used by the blood to circulate on the walls of blood vessels and is a vital vital sign of life. The purpose of this study was to determine the effect of sleep quality on blood pressure in the elderly at the Sukamakmur Community Health Center in Aceh Besar. The method used in this study is cross-sectional using purposive sampling data collection techniques. The sample in this study were 100 respondents. Data retrieval is by blood pressure measurement, and Pittsburgh Sleep Quality Index (PSQI) instrument questionnaire to determine the quality of sleep. Data analysis was performed by bivariate analysis using the Chi-Square method. The results showed there were 84.0% of respondents having poor sleep quality, and 16.0% with good sleep quality. The majority of poor sleep quality is in the category of hypertension as much as 43.0% while poor sleep quality with normal blood pressure is 41% and good sleep quality with normal blood pressure is 16%. The results of the analysis show that the correlation between the two variables is 0.049 (0.05). There is an influence between the quality of sleep and blood pressure in the elderly at the Sukamakmur Community Health Center in Aceh Besar.Keywords: Sleep quality, blood preassure, elderly